2017
DOI: 10.1111/jgs.15079
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Awareness of Deprescribing: A Population‐Based Survey

Abstract: ObjectivesTo determine older adults’ awareness of the concept of medication‐induced harm and their familiarity with the term “deprescribing.” Secondary objectives were to ascertain determinants of self‐initiated deprescribing conversations and to identify how older adults seek information on medication harms.DesignCross‐sectional population‐based household telephone survey using random‐digit dialling.SettingCanada.ParticipantsCommunity‐dwelling adults aged 65 and older (N = 2,665; n = 898 men, n = 1,767 women,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 25 publications
1
45
0
Order By: Relevance
“…We also showed that patients and caregivers were able to weigh these factors, especially evident when presented with clinical scenarios, indicating they would be able to participate in shared decision making and engage in conversations surrounding deprescribing. This is further supported by studies that show patients who were more aware of medication harm and the term “deprescribing” were more likely to initiate conversations related to deprescribing . By understanding factors that impact patients' and caregivers' perceived value of a medication, prescribers and health systems can more ably identify and prioritize medications in conjunction with patients that they would find mutually acceptable to discontinue.…”
Section: Discussionmentioning
confidence: 84%
“…We also showed that patients and caregivers were able to weigh these factors, especially evident when presented with clinical scenarios, indicating they would be able to participate in shared decision making and engage in conversations surrounding deprescribing. This is further supported by studies that show patients who were more aware of medication harm and the term “deprescribing” were more likely to initiate conversations related to deprescribing . By understanding factors that impact patients' and caregivers' perceived value of a medication, prescribers and health systems can more ably identify and prioritize medications in conjunction with patients that they would find mutually acceptable to discontinue.…”
Section: Discussionmentioning
confidence: 84%
“…Older adults varied in their interest for more information about their medications and involvement in decision making . For example, raising the topic of discontinuing a medication was initiated by only 18% of older adults in a Norwegian study, while 55% had done so in a US study and 42% in a Canadian study . The Canadian study found that initiating a deprescribing conversation was more likely in older adults who searched for information about and had an awareness of medication harms .…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies (n = 28) used qualitative methods, eg, focus groups, semistructured interviews, and Delphi approach; one used mixed methods, 41 and 9 used quantitative methods. 44,48,51,52,57,58,65,68,69…”
Section: Searches Of Electronic Databases and The Reference Lists Of mentioning
confidence: 99%
See 2 more Smart Citations